QSAR STUDY OF TESTOSTERONE DERIVATIVES USING QUANTUM CHEMICAL AND TOPOLOGICAL DESCRIPTORS: Life Sciences-Computational Chemistry - SINGH, R. K.; SINGH, ANAND; SINGH, DEEPA (International Journal of Life Science and Pharma Research, 2011)
QSAR models of testosterone derivatives, whose receptor binding affinity is known, have been developed by using maximum of four descriptors. The descriptors are heat of formation, log P, molecular weight, shape index (basic kappa, order 1), connectivity index (order 0, standard), valence connectivity index (order 0, standard), solvent accessibility surface area and molar refractivity. The best QSAR model has correlation coefficient above 0.99 and has been developed by combination of four descriptors viz. heat of formation, shape index order 1, valence connectivity index order 0 and solvent accessibility surface area. This QSAR model is very reliable and can efficiently be used for the prediction of receptor binding affinity.